LEGAL ASPECTS OF THE USE OF DIGITAL TECHNOLOGY THROUGH SHARIA ONLINE TRANSACTIONS IN TRADITIONAL MARKETS IN INCREASING COMMUNITY ECONOMY - Andi Aina Ilmih; Kami Hartono; Ida Musofiana (UNISSULA, 2019)
This research focuses on the use of digital technology through sharia online transactions in traditional markets in the City of Semarang. Then analyze the legal policies governing the use of digital technology through sharia online transactions in Indonesia and determine the impact of the use of digital technology through sharia online transactions in the Semarang traditional market. This research uses empirical legal research methods, with descriptive-analysis method. Based on research that has been done, the legal arrangements for the use of digital technology through sharia online transactions in Traditional Markets are regulated in Act Number 11 of 2008 concerning Electronic Information and Transactions (ITE) and the impact of using digital technology through sharia online transactions includes both positive and negative impacts. Positive impacts include: Industrial productivity has increased; encourage MSMEs to enter e-commerce; facilitate the promotion and marketing activities of a product; and more new services are making it easier for the economy and business. As well as the negative impacts, among others: the easier transactions are prohibited and the more cases of lawlessness occur in online trading.